Ekonomi Politik Pada Iklan Wardah Di Televisi: Analisis Wacana Kritis Norman Fairclough - Batubara, Ariyandi; Gusti Zamzami, Filyadi (UIN Sulthan Thaha Saifuddin Jambi, 2023)
Wardah is one type of cosmetics in Indonesia. Since the initial launch of this cosmetic product, it has been labeled with a religious entity. However, Wardah advertising always adapts to consumer needs. The reason is that competition between industrial companies requires them to always be adaptive and innovative in producing products, including how to convey them to consumers. Wardah advertising always follows market needs, which can be seen from the actors used and used as Wardah brand ambassadors. Starting from Norman Fairclough's perspective, Wardah's advertisement is very pragmatic. Wardah advertising follows trends among consumers. This is because the text will not be isolated from context. Wardah advertisements have recently been influenced by the context of the phenomenon of emigration and religious conversion. With this, actresses Fiera Arie, Sandara Dewi, and Ayoona Moon became advertising actors and brand ambassadors for Wardah.